Ultrasound screening in second and third trimester of pregnancy: an update - Verrotti, C.; Caforio, E.; Gramellini, et al., D. (Acta Biomedica Atenei Parmensis, 2007)
Ultrasound screening of structural fetal malformations is mainly based on the use of ultrasounds during the second trimester of pregnancy. The diagnostic sensibility of ultrasounds varies in the different multicentric studies reported in literature and is correlated to different factors: gestation period, type of malformation, number of ultrasounds performed, operator experience, etc. Third trimester ultrasounds may identify late-onset malformations and offer adequate information for postnatal assistance.